2009
DOI: 10.1002/cncr.24032
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia‐treated mesenchymal stem cells exert antitumor effects on human carcinoma cell line

Abstract: BACKGROUND:Mesenchymal stem cells (MSCs) possess the potential for differentiation into multilineages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 47 publications
2
52
2
1
Order By: Relevance
“…It has been demonstrated that hyperthermia treatment of human MSCs produced antitumor effect. Cultivation of cancer cells in the conditioned medium collected from heated MSCs exerted a suppressive effect on tumor cell growth, suggesting that hyperthermia enables tumor stromal cells to provide a sensitizing environment for tumor cells (Cho et al 2009). Further experiments are required to confirm these findings.…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that hyperthermia treatment of human MSCs produced antitumor effect. Cultivation of cancer cells in the conditioned medium collected from heated MSCs exerted a suppressive effect on tumor cell growth, suggesting that hyperthermia enables tumor stromal cells to provide a sensitizing environment for tumor cells (Cho et al 2009). Further experiments are required to confirm these findings.…”
Section: Discussionmentioning
confidence: 97%
“…More importantly, a study was carried out showing that MSCs within the tumor stroma promote breast cancer metastasis by CCL5 signaling through the chemokine receptor CCR5 expressed in the tumors (18). Our previous studies demonstrated that cytokines secreted by MSCs can influence tumor cell growth (43,44). Therefore, manipulation of the interaction between MSCs within the tumor stroma and tumor cells might improve conventional cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, human fetal skin-derived MSCs inhibited the growth of MCF-7 breast cancer cells in vitro. 52 Cho et al 53 reported that hyperthermia-treated MSCs (heattreated MSCs) exerted antitumor effects on human carcinoma cells by producing various cytokines such as interleukin (IL) ( Table 1).…”
Section: Non-engineered Stem Cells Transplantation Strategiesmentioning
confidence: 99%
“…It is said that the tumor suppression effect was due to various cytokines produced by AM-hMSCs such as granulocyte macrophage colony-stimulating factor, IL-6, neurotrophin 3, CCL18 (a chemokine), macrophage colony-stimulating factor, brain-derived neutrophic factor, granulocyte chemotactic protein (GCP-2) and conserved dopomine neutrophic factors. 53 In detail, AM-hMSCs may mediate the tumortargeting effects of immunocytes by regulating the expressions of various cytokines such as tumor necrosis factor-a and ILs. 55 For instance, ILs may help immune systems by activating natural killer cells that can directly target human cancers.…”
Section: Non-engineered Stem Cells Transplantation Strategiesmentioning
confidence: 99%